Leadership and organizational impact on employee creativity in jabodetabek startups: a mediation study - Rizki Putra; Aryana Satrya (Institute of Computer Science (IOCS), 2024)
Significant changes triggered by globalization and the COVID-19 pandemic have required adaptation and creativity in the world of work, especially in the digital era. The millennial and Z generation, which dominate the workforce today, have an essential role in creating competitive advantages and maintaining the sustainability of organizations, especially startups. This research aims to measure and analyze the influence of Perceived Authentic Leadership and Organizational Identification on Employee Creativity mediated by Work Engagement in employees who work in Jabodetabek startups. This research uses a survey-based methodology using an online questionnaire with assessments using a Likert Scale. Data from 243 respondents was analyzed using the partial least squares structural equation modeling (PLS-SEM) technique. The research results show that perceived authentic leadership and organizational identification positively affect employee creativity, both directly and through the mediation of work engagement.